Persistence of the movement of the tropical cyclones depressions In the Bay of Bengal during the premonsoon and post monsoon periods - JAYARAMAN, S.; SRINIVASAN, T. R.; SIRCAR, N. C. RAI (MAUSAM, 1966)
An examination of the tracks of cyclonic storms/depressions in the Bay of Bengal during the pre-monsoon and post-monsoon periods (April-May and October-December respectively) for the years 1891 to 1960 was made with reference to the characteristic of their direction of movements. The sea area was divided into 2 ½ degree squares for this study. The cyclonic disturbances in each of the 2 ½ degree were classified into three categories, viz., (1) clockwise curvature, a. (2) anticlockwise curvature, b and (3) persistent type, c. The relative percentage frequencies of the above types a, b and c in each of the 2 ½ degree squares for the months April-May and October-December were found out and isolines of the percentage frequencies at 20 percent intervals were drawn on the diagrams.